Applications of Chiral Cyclopentadienyl (Cpx) Metal Complexes in Asymmetric Catalysis. Issue 42 (10th September 2020) - Shaaban, Saad; Davies, Caitlin; Waldmann, Herbert
Abstract : Metal complexes containing cyclopentadienyl (Cp) ligands are versatile and robust catalysts widely applied in organic synthesis. During the last two decades chiral Cp x complexes have been applied in a variety of enantioselective transformations. Often associated with Group 9 metals (Co, Rh, Ir), chiral Cp x ligands have also been used in combination with early transition‐metals and rare‐earth elements. In this minireview asymmetric reactions that have been successfully steered with chiral Cp x ligand metal complexes are discussed according to the metal coordinated. Several ligand designs have successfully been used in a diverse array of reactions, in particular C–H functionalisation, with binaphthyl‐derived ligands leading this field. Challenges with these ligands derive from the need for their multi‐step synthesis, and recently new ligands were designed, which can be accessed in shorter sequences from readily available starting materials. Abstract : In the last two decades significant progress in enantioselective transformations employing chiral Cp ligands (Cp x ) has been made. The use of these ligands has typically been associated with Group 9 metals (Co, Rh, Ir), however the use of chiral Cp x ligands has also been reported in combination with early transition‐metals and rare‐earth elements. This minireview presents an overview of the recent asymmetric reactions that have been successfully steered with chiral Cp x metal complexes. The reactions are discussed according to the metal coordinated by the ligand.